Phylogenetic analysis revealed first report of Eleutheronema rhadinum lineage in the coastal waters of Malaysia - Atikah, N.W.; Esa, Y.B.; Rozihan, M.; Ismail, M.F.S.; Kamaruddin, I.S. (Triveni Enterprises, 2020)
To genetically identify Eleutheronema specimens and to perform phylogenetic analysis of Eleutheronema from the coastal waters of Malaysia using sequence analysis of mitochondrial Cytochrome c oxidase I (COI) gene. A total 151 samples of Eleutheronema sp. were collected from Malaysian coastal water. DNA was extracted from 25 mg caudal tissue and standard procedures were followed for COI gene amplification and sequencing. The sequences were then proceeded for the analysis of mitochondrial COI sequence by using MEGA7. A total of 20 haplotypes were found. Phylogenetic analysis identified two genealogical lineages; E. tetradactylum and E. rhadinum, respectively, harbouring 10 haplotypes each. The genetic distance range was 16%- 17%, thus supported the two lineages as distinct taxa. E. rhadinum lineage has been reported for the first time from Malaysian coastal water. Mitochondrial analysis successfully distinguished two reciprocally monophyletic taxa using COI dataset. The results also managed to provide first genetic evidence of E. rhadinumexistence in Malaysian coastal waters.